Phytochemical analysis of gisol (Kaempferia galanga) leaves extract - Criselda B. Bonifacio. 4 0 16; 5 (2005)
u
Undergraduate Thesis: (Bachelor of Science in Chemistry) - Pamantasan ng Lungsod ng Maynila, 2005.
Keywords: 2 -- 0; 6; 20; 20; 2